Beneficial effects of acetyl-DL-Leucine (ADLL) in a mouse model of Sandhoff disease - Kaya, E; Smith, D; Smith, C; Boland, B; Strupp , M; Platt, F (MDPI, 2020)
Sandhoff disease is a rare neurodegenerative lysosomal storage disease associated with the storage of GM2 ganglioside in late endosomes/lysosomes. Here, we explored the efficacy of acetyl-DL-leucine (ADLL), which has been shown to improve ataxia in observational studies in patients with Niemann–Pick Type C1 and other cerebellar ataxias. We treated a mouse model of Sandhoff disease (Hexb-/-) (0.1 g/kg/day) from 3 weeks of age with this orally available drug. ADLL produced a modest but significant increase in life span, accompanied by improved motor function and reduced glycosphingolipid (GSL) storage in the forebrain and cerebellum, in particular GA2. ADLL was also found to normalize altered glucose and glutamate metabolism, as well as increasing autophagy and the reactive oxygen species (ROS) scavenger, superoxide dismutase (SOD1). Our findings provide new insights into metabolic abnormalities in Sandhoff disease, which could be targeted with new therapeutic approaches, including ADLL.